Reducing students' ecological footprints through self-developed interventions. (December 2022) - Wagner, Claire; Gibberd, Jeremy
An increasing emphasis on taking personal responsibility for making changes to address climate change and support sustainable development is hindered by the limited tools and guidance available that enable the relationship between living patterns and environmental impacts to be readily and accurately discerned. An exception is the ecological footprint calculator that measures the global environmental impact of everyday activities. This study describes how the ecological footprint calculator is used as part of a master's course in environmental psychology to enable students to understand, change, and measure the environmental impacts of their daily activities. A case study design based on students' exercises was used to collect quantitative and qualitative data. We found relational, environment, financial, and self-efficacy themes embedded in their reflections on the intervention process. Our study supports an educational approach that requires students to self-develop, implement, and measure interventions to reduce their ecological footprint.